Keterkaitan dan Implikasi Nilai-nilai Karakter dalam Kompetensi Inti: Sebuah Analisis - Hanny Setyawati; Muhammad Zanuar Habibi; Eka Rina Febriyani (Moral : Jurnal kajian Pendidikan Islam, 2024)
This study analyzes the relationship between character values ​​and core competencies in an educational context or work environment. Character values ​​such as integrity, hard work, cooperation, and responsibility are studied in the context of how they influence and support the development of core competencies such as problem-solving abilities, leadership, and effective communication. This research uses an analytical approach to explore how strong character values ​​can form desired core competencies and influence overall performance. The results of this research provide valuable insights for educators, organizational leaders, and practitioners to understand the importance of integrating character values ​​in the development of core competencies.